(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Chronic pancreatitis is characterized by progressive pancreatic fibrosis and loss of endocrine and exocrine function. The aetiology of pain in chronic pancreatitis is unclear. It often precedes any loss of endocrine or exocrine function and any radiographically demonstrable changes in the pancreas. Aim: The primary aim of therapy is the achievement of primary pain relief and an improvement in quality of life. To analyse the efficacy & outcome of the extended drainage procedure. Technical feasibility, safety & effectivity of lateral pancreaticojejunostomy (LPJ) in selected patients Methods: Patients with chronic pancreatitis including all age groups from our tertiary care institution will be screened and selected to undergo LPJ. After obtaining valid written informed consent they will undergo surgical procedure according to the inclusion and exclusion criteria. Patients will be followed up post operatively for 6 months and the results will be evaluated and analyzed statistically. Findings: Excellent results can be expected if appropriate choice of procedure with adequate drainage is achieved during the surgical procedure Conclusion: About seventy one percent patients had significant remission of their pain with improvement in weight gain after LPJ. Among the various approaches, Laparoscopic LPJ is relatively more effective than open procedure in the immediate postoperative period in terms of less pain, early mobilisation and faster return to daily activities.